Isolation and Characterization of Constituents from The Extracts of Momordica angustisepala Aerial Parts - Hamid, Abdulmumeen Amao; Egharevba, Godshelp Osas; Issa, Shuab Bolaji; Olalere, Oluwafeyikemi Mercy; Akinloye, Bukunmi Temitope; Yakub, Yakub Tunde (Biology, Medicine, & Natural Product Chemistry, 2025)
N-hexane, ethyl acetate and methanol extracts of Momordica angustisepala were screened for the presence of metabolites, using column and thin-layer chromatographic techniques. Octadecane (1), tetradec-5-enoic acid (2), 1,2,3-propanetriyl (8Z,11â€™Z,14â€Z)tris(-8,11,14-eicostrienoate) (3), methyl oleana-5,12,15-trienoate-3Î²-acetate (4) and 1,2,3-propanetriyl (9Z,12â€™Z,15â€Z)tris(-9,12,15-uneicostrienooate) (5) are the compounds obtained from the extracts of M. angustisepala aerial parts using proton and 13C Nuclear Magnetic Resonance Spectroscopy (NMR).